STRATEGI KOMUNIKASI INTERPERSONAL MEDIA INSTAGRAM @DINKESDKI DALAM MENINGKATKAN KESADARAN MASYARAKAT SELAMA PANDEMI COVID-19 - Nuke Aliyya Tama; Sulistyawati Murdiningrum; Sri Rahayu (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
In Indonesia, social media activities have emerged a long time ago, if people can benefit from social media then many benefits are obtained such as marketing, co-workers, work connections and expanding social relations. Instagram media is currently used as a means of viewing news or information available.  People as instagram users must be good at utilizing it. For example, on the official account of the Dki Jakarta Health Office @dinkesdki which contains news about health issues, one of which is valid news related to Covid-19.  The purpose of this research is to analyze the level of public awareness related to Covid-19. This research uses qualitative research method,  the result of data from this research in the form of facts that have been found at the time of field by researchers. Health Minister Province Jakarta communication strategy is to promote health so that it can be understood and can be carried out by all people who become communion. Related to Covid-19, policies related to health regulations and how to practice in the field go back to the nature of society.  followers of instagram @dinkesDKI themselves feel the direct benefits of the platform, because it provides valid information and updates related to the Covid-19 pandemic. Instagram @dinkesDKI's strategy towards the level of public awareness related to Covid-19 can not be formulated in a valid calculation, but instagram @dinkesDKI has a good insight into people's insights related to Covid-19.